KESEIMBANGAN DAN KEADILAN EKONOMI ERA SOCIETY 5.0 PADA PERSPEKTIF MAQASID SYARIAH - Lusiana, Lusiana (STIT Sunan Giri Bima, 2024)
The Society 5.0 era presents both challenges and opportunities that are crucial in the study of technological advancements, offering the potential for increased efficiency, productivity, and innovation across various economic sectors. However, this smart technology can also create economic disparities, including access to and the ability to use technology, as well as economic balance related to distribution and income. This research also adopts a Sharia-based perspective as its conceptual framework. This paper will analyze the challenges and opportunities in achieving economic balance and justice in the Society 5.0 era, identifying strategies, policies, and implementations to create a fair and sustainable economic system in this digital transformation era. The methods used include literature studies, conceptual analysis, and case studies related to the application of Sharia principles in the context of the Society 5.0 economy. The results of this research show that economic balance refers to a condition where various elements in the economic field are in a state of equilibrium and harmony. This includes balance in supply and demand, balance in inflation and deflation, and income balance. Economic justice encompasses distributive justice, procedural justice, and compensatory justice. Economic balance and justice are essential goals to achieve stability, prosperity, and social welfare in a society.